Highly stable self-passivated MoO3-doped graphene film with nonvolatile MoOx layer - Shin, Somyeong; Kim, Seonyeong; Song, Hyeon-Kyo; Kim, Hansung; Kim, Taekwang; Du, Hyewon; Kang, Dain; Hwang, Jun Yeon; Woo, Yun Sung; Seo, Sunae (Elsevier BV, 2022)
The realization of high-performance graphene-based electronics, including transparent electrodes, flexible de-vices, and energy storage, is often hindered by the lack of adequate doping, which provides a stable and low sheet resistance. In this study, we demonstrate a highly stable MoO3-doped graphene obtained simply through a self-passivation. Graphene deposited with a 5-nm-thick MoO3 exhibited a significant decrease in sheet resistance upon annealing at 400 degrees C under a hydrogen atmosphere. Surface and structural analyses confirmed that MoO3 was converted to MoOx by thermal annealing, which consisted of mainly crystalline MoO3 and Mo4O11 with coexisting MoO2. A field-effect transistor fabricated using the MoOx-doped graphene exhibited a p-type char-acteristic similar to that of the MoO3-doped graphene. However, unlike the MoO3-doped graphene severely degraded by environment, the MoOx-doped graphene exhibited stable electrical properties after air exposure and chemical immersion owing to the chemically inert Mo4O11 and MoO2 acting as passivation layers while main-taining the p-type doping by MoO3. Thus, we expect that the highly stable MoOx-doped graphene obtained via the simple method will facilitate the fabrication and contribute to the performance reliability of various graphene-based electronic devices.